Impact of Different Time of Use Electricity Pricing Structure on Residential Consumer - Nur Azrina Mohd Azman; Md Pauzi Abdullah; Mohammad Yusri Hassan; Dalila Mat Said; Faridah Hussin; Norzanah Rosmin; Siti Maherah Hussin (Institute of Advanced Engineering and Science, 2018)
Load profile for residential users is different from commercial users where peak load occurs outside of work hours compared to working hours. Consequently, the Time of Use-based electricity price must be different not only in terms of price, but also in terms of time block structure. This paper examines the impacts of different TOU structures on TOU prices and load profiles of residential consumer. Four TOU structures are tested on the real load profile for a selected residential consumer area in Malaysia. Two elasticity factors are used for each structure to represent two different groups of users, a group that responds highly to price changes and a group that does not. The TOU price set for each structure is determined optimally subject to the following constraints; the price difference between the TOU and a fixed price per hour should be minimized and the amount of difference between price increase and price drop should be equal. From the analysis, the TOU structure with 12-time blocks provides better price signals and peak load reduction.